Temple Beth Israel Celebrates Cantor Michael Loring's 80th Birthday - Watkins, Howard::::::::: (1988)
William Leifer, Rabbi Ken Segel, ???, June Loring, Cantor Michael Loring, ?,and? In front of Holy Ark